ABOUT TECHNIQUE OF KEYNESIAN ANALYSIS FOR DYNAMIC PROCESSES IN THE ADVANCED ECONOMIES - U. T. Dzhamakeev (Модернизация, инновация, развитие, 2015)
In this paper we present improved technique for application of Keynesian analysis to the forecasting of economic dynamics of the developed countries, which is illustrated by the example of theU.S.economy. For the coming years it projects an upward trend ofU.S.economic growth, indicating an early exit from the crisis depression.